2021
DOI: 10.1002/adfm.202102420
|View full text |Cite
|
Sign up to set email alerts
|

FeNC Electrocatalysts with Densely Accessible FeN4 Sites for Efficient Oxygen Reduction Reaction

Abstract: The development of iron and nitrogen co‐doped carbon (FeNC) electrocatalysts for the oxygen reduction reaction (ORR) in proton‐exchange membrane fuel cells (PEMFCs) is a grand challenge due to the low density of accessible FeN4 sites. Here, an in situ trapping strategy using nitrogen‐rich molecules (e.g., melamine, MA) is demonstrated to enhance the amount of accessible FeN4 sites in FeNC electrocatalysts. The melamine molecules can participate in the coordination of Fe ions in zeolitic imidazolate frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(88 citation statements)
references
References 68 publications
1
78
1
Order By: Relevance
“…The oxygen reduction reaction (ORR) is a crucial electrochemical process that occurs in rechargeable metal–air batteries, fuel cells, and other energy conversion and storage devices. [ 1–5 ] However, the sluggish kinetics of the ORR, which involves four electron and proton transfer steps, seriously restricts the overall energy conversion efficiency of these devices. Currently, noble Pt‐based materials are regarded as state‐of‐the‐art electrocatalysts for the sluggish ORR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxygen reduction reaction (ORR) is a crucial electrochemical process that occurs in rechargeable metal–air batteries, fuel cells, and other energy conversion and storage devices. [ 1–5 ] However, the sluggish kinetics of the ORR, which involves four electron and proton transfer steps, seriously restricts the overall energy conversion efficiency of these devices. Currently, noble Pt‐based materials are regarded as state‐of‐the‐art electrocatalysts for the sluggish ORR.…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen reduction reaction (ORR) is a crucial electrochemical process that occurs in rechargeable metal-air batteries, fuel cells, and other energy conversion and storage devices. [1][2][3][4][5] However, the sluggish kinetics of the ORR, which involves four electron and proton transfer steps, seriously restricts the a hydrogel-derived process and found that it exhibited higher ORR activity than Co/PFC or Ni/PFC. [10] Su et al investigated the synergistic effect of Fe and Co in TM@N-C catalysts, demonstrating that alloying generates a favorable electronic environment on the surface of the material and thus improves its ORR activity.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, single metal atoms are more likely captured by graphitic carbon with rich nanopores due to abundant defects by heteroatom doping [8, 16, 35–38] . In the present study, three structures of the FeN 4 sites are considered computationally that are situated at different locations of a graphene sheet (details in the Supporting Information), on the basal plane (Fe 1 ‐1, panel (i) in Figure 1a), at the nanopore edge (Fe 1 ‐2, panel (ii) in Figure 1a), and adjacent to the nanopore (Fe 1 ‐3, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The success of N doping into carbon matrix was verified by the C N bond. 62 High-resolution N 1s spectrum displayed four component peaks at 397.8 (pyridinic N, 48.78%), 399.1 (Fe-N x , 9.80%), 63,64 400.2 (pyrrolic N, 29.13%), 401.8 eV (graphitic N, 8.85%), and 403.5 eV (oxidized N, 3.44%), proving that N was successfully doped into the carbon skeletons (Figure 3C). 65 By coordinating with pyridineand pyrrole-N, Fe can form atomically dispersed Fe-N x species.…”
Section: Materials Characterizationmentioning
confidence: 99%